Pharmaceutical cocrystal and their role in improving solid state properties of active pharmaceutical ingredients - Ameera A Radhi; Iman S Jaafar; Noor S Jaafar; Sarah M Faisal (College of Pharmacy / Mustansiriyah University, 2023)
Cocrystallization is an emerging approach for improving physico-chemical characteristics of an active pharmaceutical ingredient (API) for instance dissolution rate, solubility, stability in addition to mechanical properties without affecting their therapeutic activity. It is of great importance when other approaches like salt or polymorph formation do not encounter the estimated targets. In this review article, an outline of pharmaceutical cocrystals will be presented, with highlighting on factors affecting cocrystallization which include ∆pKa, donors and acceptors hydrogen bonds, molecular recognition point, synthon forming functional groups flexibility, dicarboxylic acid coformers carbon chain length and solvent effect, as well as and the methods for cocrystal preparation. Additionally, cocrystal characterization, dissolution pattern as well as the commercially available products were discussed.